Association Between Amygdala Volume and Trajectories of Neuropsychiatric Symptoms in Alzheimer's Disease and Dementia With Lewy Bodies - Jaramillo-Jimenez, Alberto; Giil, Lasse M.; Tovar-Rios, Diego A.; Borda, Miguel Germán; Ferreira, Daniel; Brønnick, Kolbjørn; Oppedal, Ketil; Aarsland, Dag (Frontiers in Neurology, 2021)
Introduction: The amygdala is implicated in psychiatric illness. Even as the amygdala undergoes significant atrophy in mild dementia, amygdala volume is underexplored as a risk factor for neuropsychiatric symptoms (NPS). Objective: To analyze the association between baseline amygdala volume and the longitudinal trajectories of NPS and cognitive decline in Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB) over 5 years. Methods: Eighty-nine patients with mild dementia were included (AD = 55; DLB =34). Amygdala volume was segmented from structural magnetic resonance images (sMRI) using a semi-automatic method (Freesurfer 6.0) and normalized by intracranial volumes. The intracranial-volume normalized amygdala was used as a predictor of the Neuropsychiatric Inventory (NPI) total score, ordinal NPI-item scores (0 = no symptoms, 1-3 = mild symptoms, ≥4 = clinically relevant symptoms), and Mini-Mental State Examination (MMSE) as measured annually over five years using gamma, ordinal and linear mixed-effects models, respectively. The models were adjusted for demographic variables, diagnosis, center of sMRI acquisition, and cognitive performance. Multiple testing-corrected p-values (q-values) are reported. Results: Larger intracranial volume-normalized amygdala was associated with less agitation/aggression (odds ratio (OR) = 0.62 [0.43, 0.90], p = 0.011, q = 0.038) and less MMSE decline per year (fixed effect 0.70, [0.29, 1.03] q = 0.010) but more depression (OR = 1.49 [1.09, 2.04], p = 0.013, q = 0.040). Conclusions: Greater amygdala volume in mild dementia is associated with lower odds of developing agitation/aggression, but higher odds of developing depression symptoms during the 5 years study period.